Scientific Diaspora as a Driving Force for Development in Serbia - Stopić, Srećko R.; Kozma, Robert Đ.; Pavlov, Tanja J. (Vojnotehnički glasnik / Military Technical Courier, 2013)
In the light of contemporary forms of migration and in the context of globalisation and rapid development of technology and transportation, diaspora is increasingly viewed through the transnational prism. Instead of forcedly scattered countrymen, who dream of returning to their homeland and have difficulties with the integration in the reception country, diaspora is seen as a link that connects worlds, the country of origin and the receiving country, thus enabling migration to be used for development of the community and society on the whole. Instead of return, the emphasis is on the circular exchange and transnational mobility. In this way countries of Southeast Europe are trying to transform the “brain drain”, which was particularly prominent in the 1990s, into “brain circulation” and “brain gain”. In Serbia, 1990s migration was triggered by saving lives, primarily from the painful and bloody civil wars waged in the former Yugoslavia, international isolation and NATO bombing, as well as the difficult economic situation. In that period, the particularly massive departure was that of young and educated people with the generally accepted slogan “to graduate, and then to emigrate”. However, migration of educated people and professionals, often motivated by career development and professional advancement abroad, has continued after 2000. Many young people are enabled to go abroad with the help of foreign scholarship foundations aiming at assisting development in Serbia, such as the Alexander von Humboldt Foundation AvH, German Academic Research Service DAAD, Mummert Foundation, etc. Therefore, the main objective of this paper is to determine the possibility for connection between professionals from diaspora and young students and engineers in Serbia, in order to facilitate the transfer of knowledge and their mobility and thus prevent the irreversible loss for the country. In addition to theoretical considerations of the possibility to improve cooperation with the diaspora, the paper analyses an example of successful cooperation between professionals in the metallurgical industry from Germany and professionals from Serbia, initiated by a representative of the professional diaspora. Finally, recommendations are made as to how to apply the lessons learned from the literature and practice for the development of sustainable cooperation among the professional diaspora and youth and professionals in Serbia.
Keywords: scientific potential; brain drain; Metallurgy; diaspora